2021
DOI: 10.1080/09553002.2021.2009146
|View full text |Cite
|
Sign up to set email alerts
|

Human resting-state EEG and radiofrequency GSM mobile phone exposure: the impact of the individual alpha frequency

Abstract: Purpose. With the extensive use of mobile phone (MP) several studies have been realized to investigate the effects of radiofrequency electromagnetic fields (RF-EMF) exposure on brain activity at rest via electroencephalography (EEG), and the most consistent effect has been seen on the alpha band power spectral density (PSD). However, some studies reported an increase or a decrease of the PSD, while others showed no effect. It has been suggested that these differences might partly be due to a variability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
(109 reference statements)
1
8
0
Order By: Relevance
“…The real MP was set to transmit a modulated 900 MHz GSM signal (peak 2 W, average 250 mW, pulse modulated with a duty cycle of 1/8) at its maximum power using a service software (Phoenix, Nokia Corp., Finland). Further details about the RF-EMF exposure setup are available elsewhere (Wallace et al, 2022).…”
Section: B Rf-emf Exposure and Dosimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…The real MP was set to transmit a modulated 900 MHz GSM signal (peak 2 W, average 250 mW, pulse modulated with a duty cycle of 1/8) at its maximum power using a service software (Phoenix, Nokia Corp., Finland). Further details about the RF-EMF exposure setup are available elsewhere (Wallace et al, 2022).…”
Section: B Rf-emf Exposure and Dosimetrymentioning
confidence: 99%
“…Results showed that MPs did not affect EEG signals during the exposure. Further details about dosimetry and phantom assessment are described elsewhere (Ghosn et al, 2015;Wallace et al, 2022).…”
Section: B Rf-emf Exposure and Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…But this approach may come at the cost of introducing additional variation between the sham and RF on conditions, making it more difficult to detect the actual EMF effect. Indeed, in quite some studies with a counterbalanced design no effects in the alpha band were reported 11 , 12 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…An essential strand within the literature on detecting the biological effects of EMF in vivo consists of studies that utilize the electroencephalogram (EEG) to record potential EMF induced alterations in the brain's electrical activity. Commonly, the brain is either assessed during rest, with resting-state EEG, or during specific tasks 11 , 12 , with event-related EEG 13 , 14 , while the participants are exposed to EMF. A session with EMF dosage and another session without EMF form the basis protocol for the experimental comparison to show the potential presence of EMF effects on the brain.…”
Section: Introductionmentioning
confidence: 99%